The Periodization of Establishment and Development of School Geographical Education (ХІХ-ХХ Centuries) - Shorobura, Inna (Pedagogical Discourse, 2013)
The periodization of establishment and development of school geographical education (ХІХ-ХХ centuries) are scrutinized in the article. We distinguish the following periods in the development of school geographical education: I period – XVIII c.; II period – XIX c.; III period – 1905-1920; IV period – 1920-1991; V – the modern period.